Use of the helium ion microscope in small crack fractography. (September 2022) - Field, I.; Kandare, E.; Tian, J.; Barter, S.
Highlights: Adequate cleaning of the fracture surface is necessary for high-resolution imaging. The Helium Ion Microscope utilises advanced technology for improved imaging. The Helium Ion Microscope demonstrates improved small crack resolution. Demonstrated improved imaging resolution will assist with small crack analysis. Abstract: Highly stressed aerospace structures, such as the wing attachment points and load carry-through bulkheads of fighter aircraft, often grow fatigue cracks from micro-scale discontinuities. These cracks spend much of their lives close to these discontinuities in the small crack regime. The accurate prediction of fatigue crack growth in this small crack regime leads to setting realistic inspection thresholds for the aircraft and assisting in accurate risk-based assessment of the lives of such cracks. Fractography can greatly aid the assessment of the growth of small cracks. It has traditionally been carried out using optical and Scanning Electron Microscopes to gather the necessary small crack growth rate data, however, limitations on the resolution and the surface sensitivity of these instruments restricts the gathering of crack growth rate data at small crack lengths. As an extension to the current capabilities, the newly introduced Helium Ion Microscope offers improved nano-scale resolution and topographical sensitivity. As a result, the Helium Ion Microscope offers the potential for both quantitative and qualitative analysis of small fatigue crack growth about nucleating discontinuities at resolutions previously unobtainable. This paper presents an overview of the technology and gives three different fractographic examples of its possible applications to failure analysis. These examples include extension of small crack fractography, extension of near initiation fractographic feature analysis, and extension of nano-scale feature analysis. To demonstrate these capabilities, fatigue fractures produced by experimental loading spectra that were applied to the aluminium alloy AA7050-T7451 have been investigated.